THE IMPACT OF GREEN HUMAN RESOURCES ON ECONOMIC PERFORMANCE; MEDIATED BY GREEN INPUT AND OUTPUT (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
AbstractThis study aims at empirically examining the role of GHRM in mediating the effect of green input and output on economic performance. This research used a quantitative approach. The population was SMIs (small and medium-sized industries) registered at the Ministry of Industry in West Sumatra. 200 SMIs were taken as the sample using a stratified proportional random sampling technique. The data were analyzed using a structural equation modeling technique with Smart-PLS. The results show that (i) the green HRM has an effect on green input, green output and economic performance; (ii) the green output has an effect on economic performance, but the green input has no effect on economic performance; and (iii) the green output mediates the relationship between green HRM and economic performance, but the green input does not mediate the relationship between green HRM and economic performance.